Harsh repression and crimes against humanity ongoing Fact-Finding Mission says - OHCHR (OHCHR, 2025)
The Government of Venezuela continues to engage in actions constituting the crime against humanity of persecution on political grounds, committed in connection with the crime of imprisonment or severe deprivation of physical liberty and other crimes, the UN Fact-Finding Mission on Venezuela said in its latest update on the country’s human rights situation.